Symptoms of Pesticide Intoxication Among Vegetable Farmers in Gowa Regency, Indonesia - Habibi, Habibi; Bukhari, Agussalim; Naiem, Muhammad Furqaan (Al-Sihah: The Public Health Science Journal, 2022)
Farmers and pesticides are two inseparable things. Pesticides are one the toxic chemicals in the agricultural sector and use to control pests and weeds in the process of getting maximum yields. This study aimed to determine the symptoms of pesticide intoxication in vegetable farmers in Gowa Regency, Indonesia. This type of study was an analytical survey with a cross-sectional study design. The number of samples was 42 people consisting of vegetable farmers who were still actively working as pesticide sprayers and was determined by purposive sampling. For collecting data, it used interviews and screening for poisoning symptoms. Data were processed by tabulating (mentioning each participant in the study group) following the grouping of the variables examined and analyzed using the chi-square test. The results showed that the most common symptoms of pesticide intoxication were felt by farmers, namely muscle pain, headaches, and dizziness. This study found a relationship between spraying methods, personal hygiene, and personal protective equipment to symptoms of pesticide intoxication (p<0.05). This study recommends that vegetable farmers pay attention to the proper use of pesticides to minimize pesticide intoxication in the body.